Electrifying light commercial vehicles for city logistics? A total cost of ownership analysis - Lebeau, Philippe; Macharis, Cathy; Mierlo, Joeri van; Lebeau, Kenneth (European Journal of Transport and Infrastructure Research, 2015)
Different measures are considered by the authorities to tackle the negative impacts of city logistics. Among them, battery electric vehicles are seen as a promising solution, but high purchase cost represents an important barrier to their adoption. However, these vehicles benefit also from low operational costs. This different cost structure between electric and conventional vehicles makes therefore a comprehensive cost analysis necessary for fleet managers who want to assess the real competitiveness of the vehicles. Hence, we developed a total cost of ownership model to assess the competitiveness of quadricycles and light commercial vehicles for freight transport companies. This paper presents the results for 7 battery electric vehicles, 5 diesel vehicles and 3 petrol vehicles. The results of a sensitivity analysis explored also the possible measures that can support their competitiveness. The model shows that battery electric vehicles have a better competitive position than petrol vehicles but they do not compete yet with diesel vehicles. A sensitivity analysis shows however that their total cost of ownership can become lower than diesel vehicles depending on their utilization, future market conditions or government support. Still, electric quadricycles appear to be currently an affordable solution for transport operators to adopt electric vehicles since their total costs of ownership is lower than diesel light commercial vehicles.